The self-reversal origin of the reversed remanent magnetization in the igneous rocks containing the oxidized Fe-Ti oxide solid solutions - ORLICKÝ, Oto (Contributions to Geophysics and Geodesy, 2011)
I study the magnetic and paleomagnetic characteristics of the Pleistocene toQuaternary basalts from the West Carpathian Mountains. I have revealed the existenceof the so-called self-reversal remanent magnetization bearing disordered-antiferromagneticFe-Ti phases, with the Néel temperatures of either TN = 430−450 °C (the Ti-Mgh phases)or with TN = 460−470 °C (Hem-Ilm phases). I have suggested for the first time to nameof these phases in this article. It is very important that these phases are the only sourcesof the reversed RM, of the self-reversal origin, probably of the chemical remanent magnetization(CRM) origin. The basalts of Southern Slovakia were differentiated to theseof the magnetite and Ti-rich Ti-Mt bearing rocks with normal polarity of RM, and thosewith the presence of the self-reversal RM bearing disordered-antiferromagnetic Ti-Mghphases of the TN = 430 to 450 °C, and those of the disordered-antiferromagnetic Hem-Ilmphases of the TN = 460 − 470 °C, both of only reversed RM of the self-reversal origin. Ipresent the original model based on the principe that the magnetite, hematite and Ti-richtitanomagnetite bearing rocks, without any disordered-antiferromagnetic phases, carryonly normal – positive RM. The self-reversal remanent magnetization bearing disorderedantiferromagneticmagnetic phases of Fe-Ti oxide solid solutions carry only reversed remanentmagnetization in the rocks. This model has been involved to explain the reversed ornormal RM of submarine igneous rocks published in the literature. We anticipate that inall continental or submarine reversally magnetized rocks the disordered-antiferromagneticFe-Ti phases would be revealed, either in their initial, complete developed stages, or asthe remnants of these phases.